ВОПРОСЫ ТИПОЛОГИИ В КАРАКАЛПАКСКОЙ ПРОЗЕ - Бекбергенова, М.Д. (SCIENCE and SOCIETY, 2020)
The given article deals with some issues of the typology of the XXth century's Karakalpak literature. There is analysed typological relation of the modern prose with samples of folk, moreover it is also depicted by prosaic descriptions of the folk mayerials. Typology of epic genre of Karakalpak literature of XXth century studies in comparison with epic literary texts of the XIXth century's karakalpak literature
Keywords: prose; genre; folk; typology; prosaic description; peculiarities of genre; epos; dastan (heroic epic poem); poem; kissa (poem); novel; epopee